Use of Some Asteraceae Plants for the Treatment of Wounds: From Ethnopharmacological Studies to Scientific Evidences - Carvalho, Alexsander R.; Diniz, Roseana M.; Suarez, Mariela A. M.; Figueiredo, Cristiane S. S. e S.; Zagmignan, Adrielle; Grisotto, Marcos A. G.; Fernandes, Elizabeth S.; da Silva, Luís C. N. (Frontiers in Pharmacology, 2018)
Severe wounds result in large lesions and/or loss of function of the affected areas. The treatment of wounds has challenged health professionals due to its complexity, especially in patients with chronic diseases (such as diabetes), and the presence of pathogens such as Staphylococcus aureus and Pseudomonas aeruginosa. Taking this into consideration, the development of new therapies for wound healing requires immediate attention. Ethnopharmacological studies performed in different countries have shown the use of several plants from the Asteraceae family as wound-healing agents. Evidences gained from the traditional medicine have opened new ways for the development of novel and more efficient therapies based on the pharmacological properties of these plants. In this article, we discuss the literature data on the use of Asteraceae plants for the treatment of wounds, based on the ethnopharmacological relevance of each plant. Special attention was given to studies showing the mechanisms of action of Asteraceae-derived compounds and clinical trials. Ageratina pichinchensis (Kunth) R.M. King and H. Rob. and Calendula officinalis L. preparations/compounds were found to show good efficacy when assessed in clinical trials of complicated wounds, including venous leg ulcers and foot ulcers of diabetic patients. The compounds silibinin [from Silybum marianum (L.) Gaertn.] and jaceosidin (from Artemisia princeps Pamp.) were identified as promising compounds for the treatment of wounds. Overall, we suggest that Asteraceae plants represent important sources of compounds that may act as new and efficient healing products.